Common Neurosurgical Conditions in the Pediatric Practice Recognition and Management - Greenfield, Jeffrey P.; Long, Caroline B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
This unique title is designed to illustrate and foster how a closer working relationship between pediatricians and subspecialists can make childhood medicine work more seamlessly. Despite the common lack of training for pediatricians in pediatric neurosurgery, they are challenged almost daily with caring for children with neurologic conditions. Common Neurological Conditions in the Pediatric Practice is replete with a wide range of instructional case vignettes and is organized into sections that loosely approximate the neurologic development of a child and address issues that are commonly encountered. The first section reviews neurologic development and birth related trauma commonly seen in the neonatal intensive care unit. The second part addresses findings commonly encountered by a pediatrician in a child$1 (Bs first month of life. The third section is a comprehensive review of hydrocephalus. Part four describes state of the art imaging techniques for the central nervous system in children, from pre-natal ultrasound through MRI and CT; and the fifth part consists of individual explorations of common neurosurgical conditions that many pediatricians are uncomfortable managing, including brain tumors, spasticity, and vascular lesions to use as a reference tool when caring for a complex neurosurgical patient. Finally a series of chapters related to head trauma, including sections on non-accidental trauma and concussion management, completes the text.s
Section 1: Development of the Brain and Spine -- 1 Normal Development of the Skull and Brain -- 2 The Neurologic Exam in Neonates and Toddlers -- Section 2: Newborn through Infancy -- 3 Birth Trauma to the Scalp and Skull -- 4 Brachial Plexus Injuries during Birth -- 5 Neonatal Brain Injury -- 6 Evaluation of Head Shape in the Pediatric Practice: Plagiocephaly vs. Craniosynostosis -- 7 Neurocutaneous Disorders -- 8 Cutaneous Markers of Spinal Dysraphism -- 9 Tethered Cord -- 10 Lumps and Bumps: Scalp and Skull Lesions -- Section 3: Hydrocephalus Primer -- 11 Intraventricular Hemorrhage in the Premature Infant -- 12 Neuro-ophthalmic Presentation of Neurosurgical Disease in Children -- 13 Hydrocephalus and Ventriculomegaly -- 14 Neurosurgical Considerations in Macrocephaly -- 15 Evaluation and Classification of Pediatric Headache -- Section 4: Imaging of the Pediatric Brain and Spine -- 16 Prenatal Imaging of the Fetal Brain and Spine -- 17 Prenatal Counseling for Fetal Diagnoses -- 18 Imaging of the Pediatric Brain -- 19 Radiographic Evaluation of Suspected Scoliosis -- 20 Image Gently: Radiation Exposure in Children -- Section 5: Beyond Hydrocephalus: What Pediatric Neurosurgeons Treat Most -- 21 Chiari Malformation -- 22 Pediatric Brain Tumors -- 23 Pediatric Neurovascular Disease -- 24 Pediatric Seizures -- 25 Approach to Spasticity in the Pediatric Patient -- 26 Assessment and Management of Minor Head Injuries in Toddlers and Adolescents -- 27 Non-Accidental Head Trauma -- 28 A Pediatrician$1 (Bs Guide to Concussion Management -- 29 Pathophysiology and Diagnosis of Concussion.s
Keywords: Medicine; General practice (Medicine).; Neurology; Pediatrics; Primary care (Medicine).; Medicine & Public Health; Primary Care Medicine; Pediatrics; Neurology; General Practice / Family Medicine